Pengaruh Brand Image, Brand Awareness dan Brand Trust Terhadap Minat Beli Pepsodent pada Mahasiswa Konsentrasi Kewirausahaan STIE Indragiri Rengat - Roky Apriansyah; Meilya Karya Putri; Walmi Sholihat (Universitas Batanghari, 2021)
The development of the toiletries industry in Indonesia is currently running so rapidly that it creates increasingly fierce competition, business people are also required to be more creative and have a competitive advantage compared to their competitors. The toiletry industry is one of the many industries that experience very tight competition, this can be shown by the increasing number of business actors entering this industrial sector. This study aims to determine the effect of brand image, brand awareness and brand trust on the buying interest of Pepsodent in entrepreneurship concentration students, Stie Indragiri Rengat. The population in this study were all students of the Entrepreneurship Concentration of STIE Indragiri Rengat, Indragiri Hulu Regency, Odd Semester, Academic Year 2020/2021, totaling 63 people. The sampling technique used is the census method. The results of hypothesis testing are: first, Brand Image partially influences the buying interest of Pepsodent in entrepreneurship concentration students of STIE Indragiri Rengat. Second, Brand Awareness partially affects the buying interest of Pepsodent in entrepreneurship concentration students of STIE Indragiri Rengat. Third, Brand Trust partially influences the buying interest of Pepsodent in entrepreneurship concentration students of STIE Indragiri Rengat.